Design technology in contemporary architectural practice - Holzer, Dominik (Abingdon, Oxon : Routledge, 2023)
"Design Technology in Contemporary Architectural Practice lifts the curtain to unveil how eleven world-leading design studios integrate technology (such as Computational Design, BIM and Digital Fabrication) as part of their day-to-day design exploration and delivery. Via first-hand accounts, the book offers rare insights about how these firms apply technology to purposefully disrupt and support their creative design processes, to then explore how technology gets integrated on an organisational level. The resulting practice stories are loosely tied to four chapters that discuss how Design Technology corresponds to studio culture, collaboration and delivery protocols, business opportunities, knowledge-sharing, staff empowerment, and more. The author is less interested in presenting the latest and greatest tools, instead focusing on cultural and organisational challenges and opportunities. This book will benefit both the professional market (such as design firms reflecting on their technology-use), as well as the academic context (with its critical reflection on the interface between design process and technology support)"--
Keywords: Architectural design -- Data processing; ARCHITECTURE / General; ARCHITECTURE / Professional Practice